Intestinal cytomegalovirus infection in patients hospitalized for exacerbation of inflammatory bowel disease: a 10-year tertiary referral center experience - Gauss, Annika; Rosenstiel, Simon; Schnitzler, Paul; Hinz, Ulf; Rehlen, Tobias; Kadmon, Martina; Ehehalt, Robert; Stremmel, Wolfgang; Zawierucha, Anna (European journal of gastroenterology & hepatology, 2015)
This 10-year retrospective cohort study aims to determine the prevalence and risk factors of cytomegalovirus (CMV) infection in inpatients with exacerbated inflammatory bowel disease (IBD). All patients admitted to the Department of Gastroenterology of the University Hospital Heidelberg for IBD exacerbation between January 2004 and June 2013 were enrolled. To identify the risk factors of CMV infection, infected individuals were compared with those with excluded infection. Among 297 patients with exacerbated IBD, 21 had confirmed CMV infection and 79 had excluded CMV infection, whereas the remaining patients had not been sufficiently tested for CMV. Taking into account only sufficiently tested individuals, the prevalence of CMV infection was 22.7% in ulcerative colitis and 16.0% in Crohn’s disease. The occurrence of CMV infection was associated with the following variables at admission: age of 30 years or more [odds ratio (OR) 14.29; P=0.004], disease duration less than 60 months (OR 7.69; P=0.011), a blood leukocyte count less than 11/nl (OR 4.49; P=0.041), and immunosuppressive therapy (OR 6.73; P=0.0129). CMV-positive patients remained in the hospital longer than noninfected patients (P=0.0009). In the CMV-positive cohort, a 66-year-old woman died of CMV pneumonia and sepsis, whereas there was no death in the CMV-negative cohort. Immunuosuppressive therapy and age older than 30 years were identified as the main risk factors for the development of CMV infection in exacerbated IBD. Because of the risk of death, diagnostics of CMV infection should especially be initiated in older patients on immunosuppressive therapy.